Analisis Kinerja Warehouse dan Perancangan Tata Letak: Studi Kasus Dekor Asia, Imogiri Yogyakarta - Dewi, Adhisty Kartika (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
The bamboo craft manufacturing industry is currently experiencing rapid growth. PT. Dekor Asia Jayakarya is one of the companies engaged in bamboo crafts located in D.I. Yogyakarta. PT. Dekor Asia Jayakarya has seen an increase in demand, which has led the company to expand its production capacity. This increase in production is accompanied by the addition of warehouses to accommodate products before export. The new warehouse has triggered several issues, including confusion in the incoming goods flow, the absence of designated lines for forklifts and pedestrians, and poor organization of products from production, resulting in congestion of items. Customer satisfaction with the products encompasses various aspects, including fulfillment speed, accuracy, pricing, quality, and more. The Wukirsari warehouse often struggles to meet the target fulfillment time for customer orders. This failure to meet targets has led to a decline in consumer trust in Dekor Asia. Therefore, the Wukirsari warehouse requires a performance evaluation to identify the indicators causing delays in order fulfillment.